Intertext Theory and Literary Contexts of Film I. - Malek, Petr (Iluminace, 1993)
The study deals with the newly emerging relations and contacts between literature and film, showing the necessity of modifying the classical model of relations between the two semiotic systems.
Keywords: literature and film; film theory; language and film; intertextuality